Regulation of Monocyte-Macrophage Responses in Cirrhosis—Role of Innate Immune Programming and Checkpoint Receptors - Riva, Antonio; Mehta, Gautam (Frontiers in Immunology, 2019)
Many aspects of the innate immune system have been studied in cirrhosis, and abnormalities have been described supporting both a pro-inflammatory and anti-inflammatory phenotype of myeloid cells. However, the findings of these studies vary by stage of disease and methodology. The recent description of the syndrome of acute-on-chronic liver failure (ACLF) has refined our understanding of the natural history of cirrhosis. In this context, we review the regulatory mechanisms at play that contribute to the immune abnormalities described in in advanced liver disease. Specifically, we review the evidence for epigenetic mechanisms regulating monocyte phenotype, and the role of checkpoint receptors on regulating innate and adaptive immune cell function.